Analysis Of Standby Horizon Gyro Indicator Failure On Cessna 172 Series Aircraft Using FMEA And FTA Methods At API Banyuwangi - Dharma, I Made Dwi Surya; Luwihono, Andung; Sulung, Sabam Danny; Wibowo, Untung Lestari Nur; Rahmanda, Nauffal Daffa (FTK UNSURYA, 2025)
In aviation, navigation instruments play a vital role in ensuring flight safety, particularly during adverse weather and night operations. Among these, the Standby Horizon Gyro Indicator, also known as the Attitude Indicator, is critical for displaying aircraft pitch and roll relative to the horizon. Failures of this instrument can significantly compromise safety, making systematic analysis essential. This study investigates failures of the Standby Horizon Gyro Indicator on Cessna 172 Series aircraft using Failure Modes and Effect Analysis (FMEA) and Fault Tree Analysis (FTA). Data were obtained from field observations, pilot reports, and interviews with certified technicians at API Banyuwangi. The analysis identified five primary failure modes: Low Vacuum Indicator, Not Function, Toppled/Spin, Unbalanced Gyro, and Stuck. The Toppled/Spin condition was found to be the most critical, with a Risk Priority Number (RPN) of 126. FTA revealed root causes including vacuum pump aging, contaminated filters, inadequate knowledge, complacency, lack of supervisory cross-checks, and low safety awareness. Corrective actions involve replacing worn components, cleaning filters, and applying strict safety procedures, while preventive measures emphasize scheduled maintenance, double-check protocols, and periodic safety training. The findings highlight the importance of addressing both technical and human factors to enhance reliability, improve maintenance practices, and strengthen aviation safety culture.